Metformin’s effect on metabolic dysfunction-associated steatotic liver disease through the miR-200a-5p and AMPK/SERCA2b pathway - Chen, Hang; Huang, Minshan; Zhang, Dan; Wang, Hui; Wang, Da; Li, Mengwei; Wang, Xianmei; Zhu, Rui; Liu, Jianjun; Ma, Lanqing (Frontiers in Pharmacology, 2024)
IntroductionMetformin has shown benefits in treating metabolic dysfunction-associated steatotic liver disease (MASLD), but its mechanisms remain unclear. This study investigates miR-200a-5p’s role in the AMPK/SERCA2b pathway to reduce liver fat accumulation and ER stress in MASLD.MethodsA PA cell model induced by palmitic and oleic acids (2:1) was used to assess lipid accumulation via Oil Red O and Nile Red staining. mRNA levels of miR-200a-5p and lipid metabolism genes were measured with RT-PCR, and AMPK, p-AMPK, and SERCA2b protein levels were analyzed by Western blotting. The interaction between miR-200a-5p and AMPK was studied using a luciferase reporter assay. A high-fat diet-induced MASLD mouse model was used to evaluate metformin’s effects on liver steatosis and lipid profiles. Serum miR-200a-5p levels were also analyzed in MASLD patients.ResultsIn the PA cell model, elevated miR-200a-5p and lipid metabolism gene mRNA levels were observed, with decreased AMPK and SERCA2b protein levels. miR-200a-5p mimic reduced AMPK and SERCA2b expression. Metformin treatment reduced liver steatosis and lipid deposition in mice, normalizing miR-200a-5p, lipid metabolism gene mRNA, and AMPK/SERCA2b protein levels. Elevated serum miR-200a-5p was detected in MASLD patients.DiscussionThese findings suggest that metformin alleviates lipid deposition and ER stress in MASLD through the modulation of the AMPK/SERCA2b pathway via miR-200a-5p.